2022
DOI: 10.3390/molecules27207045
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Porous Systems Based on Polylactide Loaded with Amikacin

Abstract: Three porous matrices based on poly(lactic acid) are proposed herein for the controlled release of amikacin. The materials were fabricated by the method of spraying a surface liquid. Description is given as to the possibility of employing a modifier, such as a silica nanocarrier, for prolonging the release of amikacin, in addition to using chitosan to improve the properties of the materials, e.g., stability and sorption capacity. Depending on their actual composition, the materials exhibited varied efficacy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…Another study showed that 25% amikacin sulfate could be entrapped in thiolated chitosan nanoparticles for oral delivery, and drug release was determined in 18 h [20]. Recently, polylactide matrices loaded with amikacin sulfate were able to release the amikacin over 60 days [21]. On the other hand, according to these findings of their investigation, the current study released amikacin release much uniformly that, reached 37% release in 7 h, which will be more significant to optimize the dosage to once daily because the dosage frequencies vary with pathological effects.…”
Section: Loading and In Vitro Release Profilementioning
confidence: 99%
“…Another study showed that 25% amikacin sulfate could be entrapped in thiolated chitosan nanoparticles for oral delivery, and drug release was determined in 18 h [20]. Recently, polylactide matrices loaded with amikacin sulfate were able to release the amikacin over 60 days [21]. On the other hand, according to these findings of their investigation, the current study released amikacin release much uniformly that, reached 37% release in 7 h, which will be more significant to optimize the dosage to once daily because the dosage frequencies vary with pathological effects.…”
Section: Loading and In Vitro Release Profilementioning
confidence: 99%